Subject and Tolerance. Regarding Lessing’s Nathan - Parcero Oubiña, Oscar (Revista de Filosofía, 2020)
This paper focuses on the relationship between tolerance and the underlying conception of subjectivity. It will try to argue that two conceptions of tolerance can be considered, “passive” and “active”, both derived from two conceptions of subjectivity in which the meeting with the other integrates antithetically. The work of Lessing will serve to illustrate a conception of subjectivity and, along with it, of tolerance, which is alternative to the hegemonic conception of other Enlightenment authors.